Determinants of sourcing practices in the pharmaceutical industry : the case study of FAME pharmaceuticals enterprise in Myanmar - Kaung Wai Wai; Vatcharapol Sukhotu; Supasith Chonglerttham; Sununta Siengthai; Ministry of Foreign Affairs, Norway (Pathum Thani, Thailand : Asian Institute of Technology, 2014)
Providing pro ducts in an effective and safe way has been the most important issue in pharmaceutical supply chain (PSM) because it has direct effect on the life of customers. So, the security for the supply of pharmaceutical raw materials including active pharmaceutical ingredients (APIs) and excipients is the backbone of PSM. And supplier selection and evaluation process is also one of the key activities in sourcing practices that will highlight the organization{u2019}s competitive strength in the market. Sourcing practices has been great challenge s for an organization to fit with five rights of purchasing in supply chain and to meet with the mission of the organization, for FPE, that is producing quality assurance products with continuous improvement in quality to ensure customer satisfaction. Strategic decision for sourcing of raw materials might be different in three options: in - house, sourcing from local suppliers and sourcing from international suppliers and might use all these three options like FPE. Organization{u2019}s competitive strategy, macroeconomic factors, technology factors, climatic needs of raw materials are also considerable factors in sourcing practices. This study will assess the determinants of sourcing practices in PSM which will help in maximizing the organization{u2019}s competitive strength by producing quality, efficacy and safety products. This study is a qualitative case - base d study and data are collected from in - depth interviews with respective managers about the sourcing of raw materials at FAME Pharmaceutical Enterprise in Myanmar. Secondary data are obtained from FAME official websites, research papers, Myanmar statistical year book, other books, related articles from journals and websites . This study will confirm that criteria for supplier selection have an impact on the supply chain performance and supply chain surplus via sourcing practices. Keywords: pharmaceutical supply chain, traditional medicine , sourcing practices, security of supply, Imports/domestic supply/in - house, traceability and visibility, reliability of suppliers
A project study submitted in partial fulfillment of the requirements for the Degree of Master of Business Administration, School of Management
Project (M.B.A.) - Asian Institute of Technology, 2014
Keywords: Pharmaceutical industry -- Myanmar